APLIKASI MEDIA PEMBELAJARAN BERBASIS WEB DENGAN METODE PROTOTYPE STUDY KASUS SMP NEGERI 1 CIJULANG - Dwitama Ardiwinata, Dinar; Mulyana, Dadan; Sidiq, Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
This research is entitled "Web-Based Learning Media Application for Cijulang 1 State Middle School (SMP) Using Case Study Prototype Methodology" and aims to improve the teaching and learning process in SMP through web-based learning media. using the prototype method as a software development method, which allows for continuous functional changes. The process begins with assessing student needs at SMP Negeri 1 Cijulang, followed by creating and evaluating an application prototype until it is ready for use. In short, this app focuses on learning specific subjects.